Delivery of oligonucleotides to bone marrow to modulate ferrochelatase splicing in a mouse model of erythropoietic protoporphyria. Issue 9 (20th April 2020) - Halloy, François; Iyer, Pavithra S; Ćwiek, Paulina; Ghidini, Alice; Barman-Aksözen, Jasmin; Wildner-Verhey van Wijk, Nicole; Theocharides, Alexandre P A; Minder, Elisabeth I; Schneider-Yin, Xiaoye; Schümperli, Daniel; Hall, Jonathan
Abstract: Erythropoietic protoporphyria (EPP) is a rare genetic disease in which patients experience acute phototoxic reactions after sunlight exposure. It is caused by a deficiency in ferrochelatase ( FECH ) in the heme biosynthesis pathway. Most patients exhibit a loss-of-function mutation in trans to an allele bearing a SNP that favors aberrant splicing of transcripts. One viable strategy for EPP is to deploy splice-switching oligonucleotides (SSOs) to increase FECH synthesis, whereby an increase of a few percent would provide therapeutic benefit. However, successful application of SSOs in bone marrow cells is not described. Here, we show that SSOs comprising methoxyethyl-chemistry increase FECH levels in cells. We conjugated one SSO to three prototypical targeting groups and administered them to a mouse model of EPP in order to study their biodistribution, their metabolic stability and their FECH splice-switching ability. The SSOs exhibited distinct distribution profiles, with increased accumulation in liver, kidney, bone marrow and lung. However, they also underwent substantial metabolism, mainly at their linker groups. An SSO bearing a cholesteryl group increased levels of correctly spliced FECH transcript by 80% in the bone marrow. The results provide a promising approach to treat EPP and other disorders originating from splicing dysregulation in the bone marrow.